EXPLORING THE RELATIONSHIP BETWEEN EFL STUDENTS HABIT OF LISTENING SONGS ON SPOTIFY AND THEIR VOCABULARY COMPETENCE - Diah Ayu Ambarwati; Cahya Komara (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Listening to songs has been long used by teachers in Indonesia as a part of English learning activities inside or outside the classroom in Indonesia. The goals are not just for leisure purposes but to develop students' English skills and sub-skills, for example, listening or vocabulary. The Indonesian EFL students generally like this activity, whereas many are accustomed to listening to songs as part of their daily habits. Apparently, listening to songs' habits today has been much easier since the emergence of Spotify's music application. This app is becoming more popular and is used by many EFL students in Indonesia. Some studies have exposed the benefits of listening to songs through this Spotify application to enrich the student's vocabulary knowledge or size. However, further investigation is still required to determine whether the variable of listening to song habits on this Spotify platform correlates with students' vocabulary competence. Based on that interest, this study seeks the relevance between these two variables using a quantitative correlational method. 26 students from a private high school in Depok, Indonesia were selected to participate in this study. The questionnaire instrument and vocabulary test were used in this study. The result showed a positive correlation between the two variables. Therefore, listening to English songs on Spotify has become a factor that influences students' vocabulary competence.